High-resolution genetic mapping of the ACE-linked QTL influencing circulating ACE activity. - Soubrier, F; Martin, S; Alonso, A; Visvikis, S; Tiret, L; Matsuda, F; Lathrop, G; Farrall, M (2002)
Fine-mapping of trait loci through combined linkage and association analysis is an important component of strategies designed to identify causative gene variants, particularly in situations where the trait may be influenced by one or more of many polymorphisms within the same gene. Angiotensin-1 converting enzyme (ACE) provides one of the best models for developing and testing such methodologies, as a major fraction of the heritable variation in the activity of the angiotensin-1 converting enzyme (ACE) is tightly linked to the ACE gene. Moreover, ACE contains many frequent polymorphisms that are in strong linkage disequilibrium with each other. Although none of these variants induces a significant amino-acid change, one or more, either singly or in combination, are likely to have a strong effect on the quantitative phenotype. Here, we show that measured-haplotype analysis of SNP data from a large European family cohort can be used to localise the major ACE-linked genetic factors influencing the trait to a 16 kb interval within the gene, thus limiting the number of ACE variants that need to be considered in future studies designed to elucidate their biological effects. The approaches developed will be applicable to the fine-mapping of other quantitative trait loci in humans.